(untitled) (Fiep Bulletin - online, 2011)
This work had as objective to determine the anthropometric, somatotype profile and of physical aptitude of athlete of the Amazonense Election of feminine futsal category sub-20. Years of age had been analyzed 12 girls with 18,5 average ±0,8; 55,44 ±3,24kg and 157,6 ±6,3cm. The applied tests abdominal had been modified, agility (4x4), horizontal impulse, race of speed of 20 meters and yoyo endurance test. Average abdominal resistance of 37,66 repetitions per minute. Horizontal impulse with average 187 cm In the agility test the gotten average of performance was of 5,59 seconds. In yoyo endurance test the Vo ² found was of 56,6. In the race of speed of 20 meters the average time was of 3,38 seconds. The gotten predominant somatotype characteristic is the endomorph. The lack of studies with same delineation suggests that more inquiries are carried through, in the direction to identify to the profile of players and level of motor performance for lapsing and orientation of the trainings as indicating standards for the modality.